Advanced polymeric composites via commingling for critical engineering applications. (November 2020) - V, Nayana; Kandasubramanian, Balasubramanian
Abstract: The commingled technology is one of the most effective and alternative methodologies for producing more sustainable as well as uniformly distributed natural fiber reinforced composite without inflecting the shearing strength on yarns or reinforcing natural fiber. The term commingled encompasses the materials consisting of both polymer matrix and reinforcing materials over the same fabric cross-section used for the production of highly flexible, continuous fiber-reinforced thermoplastic prepregs. Nonetheless, the increased pathlength and high melt viscosity around 500–5000 Pa s of the molten thermoplastic makes the processing more difficult compared with other thermoset plastic (usually 100 Pa s). Where the commingled hybrid yarns can be considered as one of the promising preforms employed for long fiber reinforced composite because of low cost, ease of storage and manipulation, excellent flexibility, molding capacity, reduced pressure consolidation as well as impregnation time while processing and the ability to form complex-shaped reinforced composite parts. The parameters that affect the process of commingling controls the consolidation of hybrid yarns thermoplastic composite; the degree of commingling depends on the pressure, temperature, and production speed during a fixed period. Recently commingled thermoplastic composite has become one of the possible destines for a wide array of applications in aircrafts, automotive, and sporting goods. This paper reviews types of commingled plastic composite, various processing routes, and the influence of the processing parameters, their properties, and their application. The manufacturing and development of hybrid yarns through air-jet texturing, intermingling process, are also discussed concerning the attributes of advanced composites. Graphical abstract: Image 1 Highlights: Reviewing the different types of commingled plastic composite, their manufacturing techniques, properties, and influencing parameters. Commingling imparts uniform distribution of matrix and fiber throughout the entire composite. Particular emphasis is placed on various industrial processing routes for composite manufacturing. Commingled plastic composites are broadly studied in civil engineering applications.